A mechanism design framework for hiring experts in e-healthcare. Issue 7 (8th August 2020) - Singh, Vikash Kumar; Mukhopadhyay, Sajal; Xhafa, Fatos
ABSTRACT: We investigate the problem of hiring experts from outside of the hospital(s) in e-healthcare through mechanism design with and without money. We handle the following scenarios: (1) multiple patients and multiple experts with patients having zero budget and (2) single or multiple patients and multiple experts with patient(s) having some positive budget. For the first scenario, we have proposed algorithms without money that satisfies several economic properties such as truthfulness, pareto optimality, and core allocation. Considering the second scenario, the truthful and budget feasible mechanisms are proposed. Through simulations, we have evaluated the performance and validated our proposed mechanisms.